1987
DOI: 10.1159/000261034
|View full text |Cite
|
Sign up to set email alerts
|

Ultramicro Analysis of the Fluid in Human Enamel During in vitro Caries Attack by Hydrochloric Acid

Abstract: An in vitro experimental caries model is described in which an ultramicro system of analysis was used during simulated decay to study the composition of fluid in micro wells drilled within human enamel. In this experiment, hydrochloric acid was used as the demineralizing agent because the results could be directly compared to recent bench-scale studies using a two-compartment diffusion cell. The two sets of results agree in principle and generally confirm an earlier ‘diffusion-controlled’ caries model. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 16 publications
6
28
1
Order By: Relevance
“…White and Nancollas [1977] and Driessens et al [1986] concluded that at least the majority of enamel has a solubility close to that of H A . Fluid from microwells in enamel sections undergoing demineralization with acid from the natural surface had values of IHA closed to those reported here [Vogel et al, 1987[Vogel et al, . 1988.…”
supporting
confidence: 87%
“…White and Nancollas [1977] and Driessens et al [1986] concluded that at least the majority of enamel has a solubility close to that of H A . Fluid from microwells in enamel sections undergoing demineralization with acid from the natural surface had values of IHA closed to those reported here [Vogel et al, 1987[Vogel et al, . 1988.…”
supporting
confidence: 87%
“…The success of the present approach to determine the best surface complex governing the CAP dissolution rested heavily upon the accuracy of the ion activity product calculations, and there were concerns related to some of the literature-reported equilibrium constant values ͑K CaAc ϩ , K CaH2 PO 4 ϩ , and K CaHPO 4 o ͒ and the selection of the activity coefficients. A study has been recently completed in our laboratory to establish best values for the equilibrium constants and activity coefficients for these IAP calculations (30).…”
Section: Resultsmentioning
confidence: 99%
“…The surface complex as envisaged by us is an interfacial entity formed at the surface of the equilibrating domain of CAP due to the rapid exchange of ions at the surface with those in the ambient solution. The substitution of CO 3 2Ϫ by PO 4 3Ϫ could lead to the surface complex assuming the HAP stoichiometry, although the quantitative value of MES would still be driven by the energetics of the underlying crystal domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undersaturation with respect to enamel apatite has often been suggest ed to be the rate-controlling factor in the caries process. Vogel et al [1987] observed that the fluid in their micro wells in lesions was saturated with respect to HAp. in agreement with our original supposition.…”
mentioning
confidence: 99%